One Health approach for Brucella canis: Serological and molecular detection in animal-hoarding individuals and their dogs - Schiavo, Letícia; Ribeiro, Matheus Lopes [UNESP]; de Almeida, Meila Bastos; da Cunha, Graziela Ribeiro; Santo, Giselle Almeida Nocera Espírito; Morikawa, Vivien Midori; Vicente, Acácia Ferreira; Ponsart, Claire; de Santi, Carlos Eduardo; Kmetiuk, Louise Bach; Megid, Jane [UNESP]; Biondo, Alexander Welker (Public Library of Science (PLoS), 2024)
Animal hoarding disorder (AHD) is classified as a psychiatric obsessive-compulsive condition characterized by animal accumulation and often accompanied by unsanitary conditions and animal cruelty. Although AHD may increase pathogen transmission and spread, particularly for zoonotic diseases, human and dog exposure in such cases has yet to be fully established. Accordingly, this study aimed to assess Brucella canis in 19 individuals with AHD (11 households) and their 264 dogs (21 households) in Curitiba, the eighth largest city in Brazil, with approximately 1.8 million habitants. Anti-B. canis antibodies were detected by the 2-mercaptoethanol microplate agglutination test (2ME-MAT) and by a commercial lateral flow immunoassay (LFIA), while molecular detection of previously positive seropositive samples was performed by conventional PCR. Although all the human samples were 2ME-MAT negative, 12/264 (4.5%, 95% Confidence Interval: 2.0–7.0%) dog samples were 2ME-MAT and LFIA positive, with 2ME-MAT titers ranging from 20 to 640. At least one dog in 4/21 (19.0%, 95% CI: 2.0–46.0%) households was seropositive. Despite the absence of seropositivity in individuals with AHD and the comparatively low seroprevalence in dogs, B. canis circulation and outbreaks should be considered in such human populations due to the high burden and recurrent character of B. canis exposure in high-density dog populations and the constant introduction of susceptible animals.